Fundamentals of successful newsletters : everything you need to write, design, and publish more effective newsletters - Bivins, Thomas H. (Thomas Harvey), 1947- (Lincolnwood, Ill. : NTC Business Books, 1992)
This book will help you understand and meet the needs of your readers, write lead stories, features and headlines that win and hold attention, design, illustrate, lay out, and print your newsletter, evaluate the finished product and build readership.
Keywords: Newsletters; Publishing; Newsletters -- Publishing